Effect of seaweed on physical properties of thermoplastic sugar palm starch/agar composites - Jumaidin, Ridhwan; Sapuan, S. M; Jawaid, Mohamad; Ishak, M. R; Sahari, Japar (Universiti Malaysia Pahang, Malaysia, 2016)

(untitled)
The aim of this paper is to investigate the physical properties of thermoplastic sugar palm starch/agar (TPSA) blend when incorporated with seaweed. The ratio of starch, agar, and glycerol for TPSA was maintained at 70:30:30. Seaweed with various contents (10, 20, 30, and 40 wt.%) were mixed with TPSA matrix via melt mixing before compression were molded into 3 mm plate at 140oC for 10 minutes. The prepared laminates were characterized for moisture absorption, water absorption, thickness swelling, water solubility, and density. The results showed that increasing seaweed loading from 0 to 40 wt% has led to a drop in moisture content from 6.50 to 4.96% and 9% reduction of the density. TPSA matrix showed 52.5% water uptake and 32.3% swelling whereas TPSA/seaweed composites (40 wt% loading) showed 97% water uptake and 74.8% swelling respectively. Higher water solubility was also shown by TPSA/seaweed composites (57 wt%) compared to that of the TPSA matrix (26 wt%). After 16 days of storage, the equilibrium moisture content for TPSA and TPSA/seaweed (40 wt% loading) were 23.2 and 25.2% respectively. In conclusion, TPSA/seaweed composites show good environmental friendly characteristics as a renewable material. In future, the properties of this material can be further improved by hybridization with more hydrophobic fillers for better resistance against water.